2001: a space odyssey : a novel - Clarke, Arthur C. (Arthur Charles), 1917-2008 (Hutchinson, 1968)
Behind every man now alive stand 30 ghosts, for that is the ratio by which the dead outnumber the living. Roughly 100 billion human beings have walked the planet Earth. Amazing that there are appromimately 100 billion stars in our local universe, the Milky Way.